Organic Geochemistry Characteristics of Aliphatic Hydrocarbon Fraction of Crude Oil from Tarakan Basin, North Borneo, Indonesia - Yulfi Zetra; Maulida Fitriyyah; Rafwan Year Perry Burhan; Zjahra Vianita Nugraheni (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
The study of organic geochemistry of crude oil from Pamusian field, Tarakan Basin, North Borneo has been done. The oil is fractionated by column chromatography and identified using gas chromatography-mass spectrometer (GC-MS). The presence of long chain n-alkanes, cadinane, 4β(H)-eudesmane, and 18α (H)-oleanane indicates organic matter derived from resin dammar Angiospermae family Dipterocarpaeae. It is also reported that there are drimane together with homodrimane and hopane as an indicator of bacterial input. The LHCPI value of 2.03 also indicates a high input of photosynthetic bacteria. Pr/Ph ratio of 3.76 and a drimane/homodrimane ratio of 1.058 indicating the oxic depositional environment of the sample. Isomer analysis of 18α(H)-oleanane and 17α(H),21β(H)-hopane provides information that the crude oil from Tarakan Basin is mature.